New records of atypical coloration in bats (Chiroptera) from Colombia - Buitrago-Castaño, Geraldine; Salas-Tupaz, Ginna; Patiño-Castillo, Edilson; Ávila-García, Ana Maria; Arenas-Ramírez, Michael; Reyes-Amaya, Nicolás; Zurc, Danny (Therya Notes, 2025)
In mammals, changes in melanocyte regulation have been reported to result in variation in skin and coat pigmentation, which may be the result of genetic abnormalities. These include albinism; leucism, piebaldism, melanism and hypomelanism. This paper records new species of bats with atypical colouration. Specimens deposited in Mammal Collection of the Museo de Ciencias Naturales de La Salle, Teriological Collection of the Universidad de Antioquia and Mammal Collection of the Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. The identification and classification of colour anomalies followed the criteria described by Lucati and López-Baucells (2016). From the review of the collections, 12 species of bats with atypical colouration were recorded, 7 of which represent new records of chromatic anomalies in bats for Colombia. The most reported chromatic anomaly was the presence of white spots, a condition known as piebaldism. Understanding the long-term frequency of these anomalies contributes to our knowledge of bat populations. These findings not only enhance the taxonomic inventory of Colombian bats but also raise new questions about the causes and implications of these pigmentation variations. Accurate identification and classification of such anomalies is crucial, as the inappropriate use of terms can create confusion in scientific literature.